Transnational securitization and violence: the discursive mechanism behind the pro-AKP diaspora's repression of the dissident diaspora groups in the West. Issue 3 (3rd April 2023) - Yilmaz, Ihsan; Shipoli, Erdoan; Dogru, Ahmet
ABSTRACT: Authoritarian regimes do not only target and oppress their opponents at home, they also try to repress dissident diaspora members abroad. The literature on transnational (extraterritorial) repression has shown that authoritarian regimes normally use transnational organs of the state such as intelligence services as part of their usual transnational repression activities. However, since they do not have sovereignty in the countries, their transnational repression has limits. This article argues that loyal diaspora supporters help these regimes as additional repression and violence apparatuses by trying to repress diaspora members from the same country of origin. However, the discursive mechanism behind this phenomenon has not been studied. This study aims to address this gap. Based on the competitive authoritarian Turkish case, it introduces the concept of "transnational securitization" to securitization theory. The article argues that what makes this type of securitization different is that the audience (pro-government Turkish and non-Turkish Muslim diaspora groups) is not only convinced by the securitization narrative that legitimates the use of extraordinary means that are normally undertaken by the state, but takes it upon themselves to carry on the anti-dissident repressive and violent actions. The article contributes to both transnational repression and securitization literatures.